2008
DOI: 10.1111/j.1601-5223.1992.tb00197.x
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy of the Triticeae: a historical perspective*

Abstract: The history of the Triticeae is replete with changes in generic concepts, caused by taxonomists' struggle with the task of representing its highly reticulate history within the hierarchical classification system demanded by scientific nomenclature. Disagreement over the criteria used for delimiting taxa is an additional complication. Linnaeus' goal was an easy identification scheme. Subsequent taxonomists sought to improve Linnaeus' scheme by making his genera more 'natural', a vague term encompassing both gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
5
0
1
Order By: Relevance
“…Since Elymus L. was first described as a genus by Linnaeus [ 13 ], its circumscription and taxonomy has changed through times but is still uncertain because of the huge morphological variation within and between species, the polyploid origin of the genus and the frequent spontaneous hybridizations between species [ 12 , 14 – 16 ]. Löve [ 12 ] suggested that the taxonomic treatment for Triticeae species should be based on genomic constitution, recognizing StH to be the genomes of Elymus .…”
Section: Introductionmentioning
confidence: 99%
“…Since Elymus L. was first described as a genus by Linnaeus [ 13 ], its circumscription and taxonomy has changed through times but is still uncertain because of the huge morphological variation within and between species, the polyploid origin of the genus and the frequent spontaneous hybridizations between species [ 12 , 14 – 16 ]. Löve [ 12 ] suggested that the taxonomic treatment for Triticeae species should be based on genomic constitution, recognizing StH to be the genomes of Elymus .…”
Section: Introductionmentioning
confidence: 99%
“…As highlighted, associating these fungi with species of Triticeae is not only obscured by incorrect identification of the host but also the complex taxonomy of the Triticeae tribe itself. Barkworth () states ‘There is little likelihood that there will ever be a single, universally accepted, taxonomic treatment of the Triticeae because of its highly reticulate evolutionary history and its low crossing barriers’. This complexity could also be interfering with our attempts to cluster endophyte strains with host species.…”
Section: Discussionmentioning
confidence: 99%
“…There are many different ways to view living organisms in relation to one another, and each has some advantage and disadvantage. Morphological characterization, functional grouping, ability to interbreed and genomic constitution are all equally valid and correspondingly limited (Barkworth 1992;Spooner et al 2003). Genera within the Triticeae have been subjected to repeated reorganization based on new genomic information and there remain conflicting views as to their best classification (Feuillet and Muehlbauer 2009).…”
Section: Taxonomymentioning
confidence: 99%
“…The historic fluidity of generic and morphological designation within the Triticeae makes this clarification especially important, and difficult. There have been significant reorganizations based on genomic data, and a unified concept of this tribe has not yet solidified (Dewey 1983;Löve 1984; Barkworth and Dewey 1985;Barkworth 1992;Wang 1992;Hsiao et al 1995;Li et al 2007;Barkworth et al 2009). This reorganization has an impact on nothogenera, hybrids of two or more established genera, which can lead to confusion, as in the case of 9Agrotriticum Cif.…”
Section: Taxonomymentioning
confidence: 99%
See 1 more Smart Citation